El Riesgo Tecnológico de la Información para Empresas Fintech (2020)
This article talks about Fintech companies, the services they offer and the great challenges they face in the development of their activity; In this way, it seeks to identify the contribution that from the systems audit can be made to provide advice that can minimize the impact of technological risk; particularly with regard to the confidentiality, availability and integrity of the information. An example is also described in which the technological risk materialized, how it impacted the company, the end users and the actions that were subsequently taken to repair the damage caused. The documentary exploration carried out in the university's databases leads to the identification of international frameworks and standards such as ISO 27001 and the OWASP framework that seek for organizations to manage information security and in which Fintech can be supported.